An Easy‐to‐Implement Toolkit to Create Versatile and High‐Performance HASEL Actuators for Untethered Soft Robots. Issue 14 (11th June 2019) - Mitchell, Shane K.; Wang, Xingrui; Acome, Eric; Martin, Trent; Ly, Khoi; Kellaris, Nicholas; Venkata, Vidyacharan Gopaluni; Keplinger, Christoph
Abstract: For soft robots to have ubiquitous adoption in practical applications they require soft actuators that provide well‐rounded actuation performance that parallels natural muscle while being inexpensive and easily fabricated. This manuscript introduces a toolkit to rapidly prototype, manufacture, test, and power various designs of hydraulically amplified self‐healing electrostatic (HASEL) actuators with muscle‐like performance that achieve all three basic modes of actuation (expansion, contraction, and rotation). This toolkit utilizes easy‐to‐implement methods, inexpensive fabrication tools, commodity materials, and off‐the‐shelf high‐voltage electronics thereby enabling a wide audience to explore HASEL technology. Remarkably, the actuators created from this easy‐to‐implement toolkit achieve linear strains exceeding 100%, a specific power greater than 150 W kg −1, and ≈20% strain at frequencies above 100 Hz. This combination of large strain, extreme speed, and high specific power yields soft actuators that jump without power‐amplifying mechanisms. Additionally, an efficient fabrication technique is introduced for modular designs of HASEL actuators, which is used to develop soft robotic devices driven by portable electronics. Inspired by the versatility of elephant trunks, the above capabilities are combined to create an untethered continuum robot for grasping and manipulating delicate objects, highlighting the wide potential of the introduced methods for soft robots with increasing sophistication. Abstract : Here, an easy‐to‐implement toolkit to rapidly prototype and manufacture various designs of HASEL actuators that feature large strain, extreme speed, and high specific power is introduced. Additionally, a portable, multichannel high‐voltage power supply is created for untethered operation of these actuators. The above capabilities are combined to construct an untethered continuum robot for grasping and manipulation.